A Phase II Trial of Selinexor, an Oral Selective Inhibitor of Nuclear Export Compound, in Abiraterone‐ and/or Enzalutamide‐Refractory Metastatic Castration‐Resistant Prostate Cancer. (27th February 2018) - Wei, Xiao X.; Siegel, Adam P.; Aggarwal, Rahul; Lin, Amy M.; Friedlander, Terence W.; Fong, Lawrence; Kim, Won; Louttit, Mirela; Chang, Emily; Zhang, Li; Ryan, Charles J.
Abstract : Lessons Learned : In abiraterone‐ and/or enzalutamide‐refractory metastatic castration‐resistant prostate cancer (mCRPC) patients, selinexor led to prostate‐specific antigen and/or radiographic responses in a subset of patients, indicating clinical activity in this indication. Despite twice‐a‐week dosing and maximal symptomatic management, selinexor was associated with significant anorexia, nausea, and fatigue in mCRPC patients refractory to second‐generation anti‐androgen therapies, limiting further clinical development in this patient population. This study highlights the challenge of primary endpoint selection for phase II studies in the post‐abiraterone and/or post‐enzalutamide mCRPC space. Background: Selinexor is a first‐in‐class selective inhibitor of nuclear export compound that specifically inhibits the nuclear export protein Exportin‐1 (XPO‐1), leading to nuclear accumulation of tumor suppressor proteins. Methods: This phase II study evaluated the efficacy and tolerability of selinexor in patients with metastatic castration‐resistant prostate cancer (mCRPC) refractory to abiraterone and/or enzalutamide. Results: Fourteen patients were enrolled. Selinexor was initially administered at 65 mg/m 2 twice a week (days 1 and 3) and was subsequently reduced to 60 mg flat dose twice a week (days 1 and 3), 3 weeks on, 1 week off, to improve tolerability. The median treatment duration was 13 weeks. At a median follow‐up of 4 months, two patients (14%) had ≥50% prostate‐specific antigen (PSA) decline, and seven patients (50%) had any PSA decline. Of eight patients with measurable disease at baseline, two (25%) had a partial response and four (50%) had stable disease as their best radiographic response. Five patients (36%) experienced serious adverse events (SAEs; all unrelated to selinexor), and five patients (36%) experienced treatment‐related grade 3–4 AEs. The most common drug‐related adverse events (AEs) of any severity were anorexia, nausea, weight loss, fatigue, and thrombocytopenia. Three patients (21%) came off study for unacceptable tolerability. Conclusion: Selinexor demonstrated clinical activity and poor tolerability in mCRPC patients refractory to second‐line anti‐androgenic agents.